Re-reading the Power of Satire: Isaiah’s ‘Daughters of Zion’, Pope’s ‘Belinda’, and the Rhetoric of Rape - Miles, Johnny (2006)
This essay’s semiotic and feminist approach proposes a re-reading of the ‘daughters of Zion’ poem (Isa. 3.16-4.1) as a rape text. Analysis of such a text (including intertextuality with Alexander Pope’s The Rape of the Lock) with deleterious effects for a rape culture reveals the interplay of satire with its poetics of rape, the misogynist biases actuating the sexual violence of its rape rhetoric, and the necessity to re-inscribe valuation of the feminine in such a text of terror vis-à-vis a rape culture. This poetic satire possesses no ideological neutrality as its androcentric nature (en)genders the (male) poet and Yhwh to (circum)(in)scribe the ultimate fate of these women as rape victims after having mocked them with sexist stereotypes. Nonresistance to this textual marginalization of Woman as ‘other’ tacitly succumbs to this text’s power to interpellate female readers as immasculated victims and male readers as salacious voyeurs, thus coopting readers in the perpetual ethos of violence against the feminine. The resistant act of re-reading such a textual act of violence, however, empowers by unveiling it as an abuse of power and liberates by voicing advocacy for the suffering silent demeaned, devalued, and dehumanized.
Keywords: rereading; Objectification; economy of gender; Rape culture; emasculation; Semiotics